DAMPAK KONVERSI PERKEBUNAN KELAPA SAWIT KE PERKEBUNAN JERUK DI KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT - Minarti Minarti; Ahyuni Ahyuni (JURUSAN GEOGRAFI FIS UNP, 2021)
The research objectives were to determine land conversion from oil palm to oranges, the size of employment opportunities for oil palm and oranges and to determine the impact of conversion on income and employment opportunities. This research uses descriptive research type with a quantitative approach, namely the data obtained from a sample of the study population is analyzed by statistical methods used. Data collection methods are observation, interview and documentation. Types of data are nominal and ratio data. Sampling takes into account land owners who convert. The results of the study were dry land agriculture experienced changes as a whole, open land was reduced by 0.4%, rice fields were reduced by 7.72%, swamps were changed as a whole, secondary swamp forests experienced changes as a whole, secondary forests experienced changes by 10.82%, oranges experienced changes. addition of 18.34%, addition of residential land 0.98%, addition of settlements 49.48% and overall reduction of mixed farming. Oil palms have more opportunities for employment than oranges. The yield of oil palm revenue was 1,014,900,000 and the receipt of oranges in three plants was 973,200,000.